Protective and therapeutic experience of perioperative safety in extremely elderly patients with biliary diseases. Issue 21 (28th May 2021) - Zhang, Zongming; Zhao, Yue; Lin, Fangcai; Liu, Limin; Zhang, Chong; Liu, Zhuo; Zhu, Mingwen; Wan, Baijiang; Deng, Hai; Yang, Haiyan; Jiao, Lijun; Xie, Xiyuan
Abstract : Abstract: To explore the protective and therapeutic measures of improving perioperative safety in extremely elderly patients with biliary diseases, so as to improve the therapeutic efficacy of surgery. A retrospective case–control study of 412 elderly patients with biliary diseases was carried out from July 2013 to July 2019. Seventy eight cases were divided into the high age (HA) group (≥80 years) and 334 into the middle–low age (MLA) group (60–79 years). In the HA compared with MLA group, Preoperative coexisting diseases: the occurrence of coexisting coronary heart disease (CHD), hypertension, chronic bronchitis with emphysema, hypoproteinemia, and anemia were significantly increased; Laboratory examinations: function of liver, kidneys, heart, lungs, and blood coagulation significantly declined; Surgical procedures: open cholecystectomy with transcystic common bile duct (CBD) exploration significantly higher, while laparoscopic cholecystectomy significantly lower; Operative effects: intraoperative blood loss, operation time, postoperative hospital stay, and length of hospitalization significantly increased or prolonged; Postoperative complications: postoperative respiratory failure, pulmonary infection, anemia and electrolyte disorder significantly increased; Therapeutic outcomes: no significant difference in the therapeutic effects. Although the surgical risk was significantly increased, there was no significant difference in the therapeutic efficacy in the HA compared with MLA group, suggesting that surgical treatment in extremely elderly patients with biliary diseases is safe and feasible. The key is to actively treat preoperative coexisting diseases, strictly adhere to surgical indications, reasonably select surgical procedures, precisely perform the operation, closely monitor and control intraoperative emergencies, timely prevent and treat postoperative complications, so as to improve the perioperative safety of extremely elderly patients with biliary diseases.